A novel mechanism - smart morphing façade system - to mitigate wind-induced vibration of tall buildings. (15th January 2023) - Hou, Fangwei; Sarkar, Partha P.; Alipour, Alice
Abstract: Wind-induced vibration plays a significant role in the design of tall buildings, primarily due to serviceability requirements for occupant comfort and structural safety. As a result, several approaches have been developed to address this concern. This paper describes a novel control mechanism, a smart-morphing-façade ( Smorphacade ) system, using the concept of an aerodynamically modified building façade to mitigate wind-induced vibration of tall buildings. Compared to a fixed-façade system, since a Smorphacade can be dynamically modified in real time based on rapidly-changing wind speed and wind direction during a windstorm, it can be further developed into an active control system. The Smorphacade is comprised of a set of circular ducts embedded in a flat plate and arranged in a matrix formation that is fixed on the original façade but with a gap between the two facades. Each circular-shaped duct is comprised of two parts, a fixed base with alternate open and closed surfaces shaped like a fan-blade and a rotating part similar in shape like the fixed one but placed inside the fixed one and capable of rotation by a protruding fin. By rotating the fin, the porosity of the duct and the fin inclination angle can be simultaneously changed, enabling flow control through the duct. The performance of a Smorphacade system in different configurations was studied using the CAARC standard tall-building model under atmospheric boundary layer wind; its effectiveness in reducing building response was examined by comparing the results of a building with a Smorphacade system to those from one without it. It was found that the effectiveness of the Smorphacade system in reducing the average combined vibration among all three directions (2 transverse and 1 torsional) varied between 16.7 and 18.6%, with a maximum reduction of 32% and 59.7% in across-wind direction and torsional direction, respectively, depending on factors such as Smorphacade configuration, wind speed, and angle of attack.